High dynamic range capillary electrophoresis method for sensitive detection of low-frequency driver mutations - Nobue Tamamura; Yoshihiko Hagiwara; Hirokazu Kato; Yusuke Ono; Kenji Takahashi; Kazuya Koyama; Hiroki Sato; Tetsuhiro Okada; Hidemasa Kawabata; Yu Ohtaki; Chiho Maeda; Miyuki Mori; et al. (Scientific Reports)
Abstract Cancer genomics aims to personalize treatments by identifying genetic abnormalities in cancer cells. However, current analytical techniques face limitations in simplicity and cost-effectiveness. To address these issues, we developed an enhanced capillary gel electrophoresis (CE) sequencer using a fluorescence-acquisition technique called “HiDy” (High Dynamic range) (HiDy-CE). The HiDy-CE reduces the hardware binning region size and increases the number of regions on a charge-coupled device image sensor, expanding the dynamic range and reducing saturation risk. By applying the multi-base primer extension method to the HiDy-CE with control DNA containing known mutations, we detected variant allele frequencies (VAFs) as low as 0.5% for major KRAS hotspot mutation at codon 12 and 13. With 10 ng of DNA from small tissues obtained via fine-needle biopsy from patients with suspected pancreaticoduodenal tumors, HiDy-CE produced equivalent VAFs in KRAS compared with targeted amplicon sequencing. This demonstrated the world’s first capability of detecting mutations below 1% on CE using pathological specimens, leveraging its wide dynamic range. With only 2 ng of input DNA, the HiDy-CE provided results highly concordant with digital PCR with minimal non-specific noise. These findings underscore the HiDy-CE’s potential for sensitive detection of oncogenes such as KRAS, facilitating pre-testing before comprehensive genome profiling.